“Falsetto Tenor’ in vocal music Teaching in China - Longji, Peng; Pattananon, Nicha; Charoensloong, Thitinun (Journal of Modern Learning Development, 2023)
The theory of falsetto tenor training is a relatively weak link in Chinese vocal music teaching theory, which is related to the practice of falsetto tenor singing in China. The overall quality of China's vocal music industry and the tradition of emphasizing practice and light theory. Whether training vocal teachers or cultivating singing actors, Vocal music teaching is a theoretical, technical, and practical art. More theoretical learning is needed to become a singer, but the lack of correct theoretical guidance often leads vocal learners astray. With the development of the times and the continuous improvement of the requirements for teaching, the ways and methods to achieve the purpose and complete the task are also constantly updated, and the teaching theory of falsetto tenor singing will continue to improve with the progress of society. Since the origin and development of the falsetto tenor are all in foreign countries, foreign scholars have studied the historical development of the singing technology and style of the falsetto tenor relatively perfectly. Most of their research has been analyzed from the identification, development history, characteristics, training methods, and other aspects of the falsetto tenor.